Repeated vaccinations do not improve specific immune defenses against Hepatitis B in non-responder health care workers - Zaffina, Salvatore; Marcellini, Valentina; Santoro, Anna Paola; Scarsella, Marco; Camisa, Vincenzo; Vinci, Maria Rosaria; Musolino, Anna Maria; Nicolosi, Luciana; Rosado, M. Manuela; Carsetti, Rita (Vaccine, 2014)
Hepatitis B is a major infectious occupational hazard for health care workers and can be prevented with a safe and effective vaccine. The serum titer of anti-HBsAg antibodies is the most commonly used correlate of protection and post-vaccination anti-HBsAg concentrations of ≥10mIU/ml are considered protective. Subjects with post-vaccination anti-HBsAg titers of <10mIU/ml 1–6 months post-vaccination, who tested negative for HBsAg and anti-HBc, are defined as non-responders. The question of whether non-responders should be repeatedly vaccinated is still open. The aim of the study was to (i) evaluate the distribution of lymphocyte subpopulations and the percentage of HBsAg-specific memory B cells in responders and non-responders (ii) assess whether non-responders can be induced to produce antibodies after administration of a booster dose of vaccine (iii) determine whether booster vaccination increases the number of specific memory B cells in non-responders. Combining flow-cytometry, ELISPOT and serology we tested the integrity and function of the immune system in 24 health care workers, confirmed to be non-responders after at least three vaccine injections. We compared the results with those obtained in 21 responders working in the same institution. We found that the great majority of the non-responders had a functional immune system and a preserved ability to respond to other conventional antigens. Our most important findings are that the frequency of HBsAg-specific memory B cells is comparable in non-responders and controls and that booster immunization does not lead either to antibody production or memory B cell increase in non-responders.